Effect and safety of pemafibrate for patients with type 2 diabetes mellitus and hypertriglyceridemia: a retrospective analysis of clinical data - Aki Okamoto; Hirohide Yokokawa; Tomoko Nagamine; Kento Goto; Hiroshi Fukuda; Teruhiko Hisaoka; Toshio Naito (BMC Endocrine Disorders)
Abstract Objectives Fibrates are suitable for the treatment of patients with high triglyceride (TG) levels. Although pemafibrate (PEMA) has been reported to have beneficial and pleiotropic actions, clinical examinations of the efficacy of PEMA for Japanese patients with hypertriglyceridemia are still limited in actual clinical settings. The aim was to evaluate the efficacy of PEMA by analyzing data from diabetic patients treated with PEMA in clinical practice. Methods Patients with type 2 diabetes mellitus and hypertriglyceridemia who were started on PEMA for at least 3 months were included in the analysis. Changes in lipid metabolism, liver function, renal function, and blood tests from before to after 3 months of PEMA treatment were evaluated. Results A total of 100 eligible patients were included in the analysis (72 males, mean age 52.9 years). TG levels decreased significantly, and high-density lipoprotein cholesterol levels increased significantly after 3 months of therapy. Low-density lipoprotein cholesterol levels were not significantly changed. Liver-related parameters showed a significant decrease. In addition, a significant decrease in creatinine levels was found in patients switching from other fibrates. There were no severe adverse events. Conclusion PEMA showed beneficial effects on lipid metabolism and liver function. The improvement of lipid metabolism was found in patients switching from other fibrates. It is possible that PEMA may improve lipid metabolism in patients with hypertriglyceridemia. Clinical trial number Not applicable.